Pengembangan Media Edukasi Melalui Model ADDIE (Motion Graphic Tata Cara Pembayaran PBB di Kantor BAPENDA Kota Batam) - Evaliata Br Sembiring; Novia Sukma (Politeknik Negeri Batam, 2023)
Since the Covid-19 pandemic, the role of technology has increased, especially in the dissemination of information, educational media, and activities in other forms of digitalization. Along with this, public services also need to be continuously improved. One of the government services of the Batam City Regional Revenue Agency related to the PBB payment method at the Batam City BAPENDA office still needs to be improved, especially for problems in payments. One of the digital media that can be used for this problem is educational media for the public in the form of motion graphics. The development of educational media applies the ADDIE model. The results showed that there was an increase in public knowledge of PBB payments by 28%. Assessment based on perception, learning and product performance, obtained 98.88%, which means the product can be used as an educational medium for PBB payment procedures, especially at the BAPENDA office in Batam.